A Hybrid Approach to Fabricated Nanowire-Nanoparticle Composites of a Co-W Alloy and Au Nanoparticles. Issue 7 (1st January 2016) - Vernickaite, E.; Bubniene, U.; Cesiulis, H.; Ramanavicius, A.; Podlaha, E. J.
Abstract : Co-W nanowires were fabricated by pulsed electrodeposition from a citrate-glycine electrolyte onto rotating cylinder electrodes and into nanoporous polycarbonate membranes. The characterization of the electrodeposition conditions and alloy composition of electrodeposited Co-W alloy thin films were determined and used to guide conditions to electrodeposit the nanowires. Gold nanoparticles of 50 nm size were also added to the electrolyte and deposited during electrodeposition of the Co-W alloy nanowires, embedded within, and attached to the nanowire tip, introducing a novel procedure to attached nanoparticles onto nanowires.